2,2-Bis(4-Hydroxyphenyl)-1-Propanol—A Persistent Product of Bisphenol A Bio-Oxidation in Fortified Environmental Water, as Identified by HPLC/UV/ESI-MS - Małgorzata Drzewiecka; Monika Beszterda; Magdalena Frańska; Rafał Frański (Toxics, 2021)
Biodegradation of bisphenol A in the environmental waters (lake, river, and sea) has been studied on the base of fortification of the samples taken and the biodegradation products have been analyzed using HPLC/UV/ESI-MS. Analysis of the characteristic fragmentation patterns of [M-H]− ions permitted unambiguous identification of the biodegradation products as 2,2-bis(4-hydroxyphenyl)-1-propanol or as p-hydroxyacetophenone, depending on the type of surface water source. The formation of 2,2-bis(4-hydroxyphenyl)-1-propanol was much more common than that of p-hydroxyacetophenone. Moreover, 2,2-Bis(4-hydroxyphenyl)-1-propanol has not been further biodegraded, in contrast to the p-hydroxyacetophenone, which was further mineralized. It has been proved, for the first time, that 2,2-bis(4-hydroxyphenyl)-1-propanol can be regarded as persistent product of bisphenol A biodegradation in the fortified environmental waters.